To the lighthouse - Woolf, Virginia, 1882-1941 (Mariner classics, 1989)
At their holiday home in Cornwall, a distant lighthouse holds a haunting attraction for the members of an Edwardian family as disillusionment, turmoil, and a world on the brink of war plague the family's relationships.